2017
DOI: 10.4067/s0718-381x2017000200001
|View full text |Cite
|
Sign up to set email alerts
|

Stature Estimate by the Upper Arch: Carrea´s Method Modified

Abstract: Odontostomat., 11(2):123-127, 2017.ABSTRACT: The Carrea's index is an alternative to estimate the human stature. However, in cases when the jaw is affected, this technique becomes impracticable. Expanding the use of the Carrea's index, by extending it to the upper elements, would increase the chances of the method, especially in cases when only the skull is available for analysis. The aim of the study was to test a new denominator for Carrea's index, so that it could be used for the upper arch, aiming at a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
0
6
2
3
Order By: Relevance
“…By using the modified Carrea's method, we found 51.6% of agreement between the estimated and actual height. This percentage is lower than that found by Lima et al 2 when analyzing different denominators to propose the modification of the mathematical formula. Lima et al 2 observed 63.6% of agreement, which led them to select the denominator of 2.55 for application of the formula in the upper teeth.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…By using the modified Carrea's method, we found 51.6% of agreement between the estimated and actual height. This percentage is lower than that found by Lima et al 2 when analyzing different denominators to propose the modification of the mathematical formula. Lima et al 2 observed 63.6% of agreement, which led them to select the denominator of 2.55 for application of the formula in the upper teeth.…”
Section: Discussioncontrasting
confidence: 62%
“…This percentage is lower than that found by Lima et al 2 when analyzing different denominators to propose the modification of the mathematical formula. Lima et al 2 observed 63.6% of agreement, which led them to select the denominator of 2.55 for application of the formula in the upper teeth. However, in a second stage of their research in which they proposed to test the new formula, concordance percentages varied according to dental position and sex, somehow closer to what we found in our study: aligned hemiarches -34.7% for males and 42.3% for females; and hemiarches with crowding -65.0% for males and 51.7% for females.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations